Das Anna und ihr Hund.: Weibliche Hundenamen im Neutrum? - Baumgartner, Gerda; Busley, Simone; Fritzinger, Julia; Martin , Sara (Linguistik Online, 2021)
In numerous German dialects and in Luxembourgish women or girls are referred to in the neuter. This raises the question whether this is also the case for female animals. Based on data from the research project “Das Anna und ihr Hund – Weibliche Rufnamen im Neutrum”, the present article examines the gender of names and pronouns referring to dogs. Dogs today are no longer kept primarily to perform functions (guard dog, herding dog) but rather as pets and companions. This is also reflected in the fact that dogs are given names. In general, these clearly mark the sex of the dog.In the dialects we investigated pronouns, which refer to female dogs, are predominantly masculine, not feminine or neuter. Sex-specific appellatives are not used either. In addition, the assignment of the neuter gender to dogs’ names (e. g. s Frida) occurs much less frequently than to first names of women (e. g. s Anna). The functions of the socio-pragmatic neuter when referring to women, such as marking age, status, or gender roles, rarely appear to play a role when referring to dogs. Only in Luxembourgish, where the neuter primarily marks female sex, are female animals referred to more often with neuter forms.